2015
DOI: 10.1111/socf.12209
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Associations' Impact on the Composition of Active Members' Social Networks: Not an Either/Or Matter

Abstract: Membership in voluntary associations is often assumed to have a homogenizing or diversifying impact on the social composition of members' personal relations. In this study, we examine these assertions empirically in a sample (n = 818) comprising active members of voluntary associations in a typical midsized Swedish community. We investigate whether people whom active members of voluntary associations have met through their voluntary activities are more or less likely to share their social characteristics than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Similarly, respondents who practiced more sports were more likely to report more friends. This finding is supported by previous research that found larger social networks among people who were members of voluntary organizations (Farkas and Lindberg, 2015;Putnam, 2000;Rotolo, 2000).…”
Section: Combining Both Experiments: Number Of Reported Friends and Q...supporting
confidence: 86%
See 2 more Smart Citations
“…Similarly, respondents who practiced more sports were more likely to report more friends. This finding is supported by previous research that found larger social networks among people who were members of voluntary organizations (Farkas and Lindberg, 2015;Putnam, 2000;Rotolo, 2000).…”
Section: Combining Both Experiments: Number Of Reported Friends and Q...supporting
confidence: 86%
“…Those measures had been collected in a welcome survey, shortly after the registration of each new panel member. The requested indicators had been found to correlate with social network size in previous studies: employment status (Edin et al, 2003;Munshi, 2003), living in an urban or rural area (Oliver, 2000;Remmer, 2010), the number of medical conditions (Michael et al, 1999;Schaefer et al, 1981), and participating in voluntary organizations (Farkas and Lindberg, 2015;Putnam, 2000;Rotolo, 2000), which we tried to measure with the number of team sports respondents exercised.…”
Section: Supplementary Information For Selection Bias Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A good or bad personal relationship among managers from both parties is one of the reasons which determine whether the alliance is efficient or not (p. 324) Chen and Pan (2009) Informal SR (also known as informal relations) Sousa (2005) The identified definitions emphasize complex social norms and mutual obligations (Serra, 2011), common values and common interests (Mikkola, 2008;Tucker, 2010) connecting individuals. Importantly, SR are also characterized by the awareness of the need to comply with these norms, obligations, interests, values or awareness of being a member of a given group (Farkas & Lindberg, 2015). Also, it should be noted that SR are related to elements of social and/or cultural anthropology (such as shared ethnic identity, language, religion, the history of people involved in the relationship, and the above-mentioned cultural and social norms) because they are usually based on kinship and/or a common place of residence (Farkas & Lindberg, 2015).…”
Section: Conceptualization Of Social Relationshipsmentioning
confidence: 99%
“…Numerous scholars have identified positive relationships between affiliation with voluntary associations and members’ political and/or civic engagement beyond their organizations (Beck and Jennings ; Coleman ; Flap ; Kwak, Shah, and Holbert ; Pollock ; Walker ). Despite a disagreement on the strength of the relationship due to the type and the number of organizations that people are affiliated with (Farkas and Lindberg ; Glanville ), the general argument is that when people are involved in voluntary associations, they are likely to participate in political or social affairs beyond their organizations because they acquire the human, social, and cultural capital needed for civic engagement through participation in such organizations (Wilson and Musick ). This claim has been elaborated by diverse mediating factors that promote such political or civic engagement, including a core group of people to mobilize other members (Rosenstone and Hansen ), social capital (Putnam ), and sense of community (Davidson and Cotter ).…”
Section: Voluntary Associations and Civic Engagementmentioning
confidence: 99%